2006
DOI: 10.1029/2005jd006458
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of volatile organic compound evaporative emissions from motor vehicles

Abstract: [1] A chemical mass balance approach is used to determine the relative contributions of evaporative versus tailpipe sources to motor vehicle volatile organic compound (VOC) emissions. Contributions were determined by reconciling time-resolved ambient VOC concentrations measured downwind of Sacramento, California, in summer 2001 with source speciation profiles. A composite liquid fuel speciation profile was determined from gasoline samples collected at Sacramento area service stations. Vapor-liquid equilibrium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
83
2
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(94 citation statements)
references
References 21 publications
8
83
2
1
Order By: Relevance
“…The increased emissions during hot periods were attributed to light hydrocarbons that are associated with headspace evaporative emissions. These results are generally consistent with an ambient source apportionment study that estimated a 6.5% AE 2.5% increase in the contributions of evaporative emissions from motor vehicles per degree Celsius increase in maximum temperature (Rubin et al, 2006). Although the NMHC emission rates predicted by all three models were in good agreement with measurements during cool periods, the running evaporative emissions for all models exhibited insufficient sensitivity to temperature during hot periods, especially MOVES.…”
Section: Discussionsupporting
confidence: 79%
“…The increased emissions during hot periods were attributed to light hydrocarbons that are associated with headspace evaporative emissions. These results are generally consistent with an ambient source apportionment study that estimated a 6.5% AE 2.5% increase in the contributions of evaporative emissions from motor vehicles per degree Celsius increase in maximum temperature (Rubin et al, 2006). Although the NMHC emission rates predicted by all three models were in good agreement with measurements during cool periods, the running evaporative emissions for all models exhibited insufficient sensitivity to temperature during hot periods, especially MOVES.…”
Section: Discussionsupporting
confidence: 79%
“…Other studies have shown linkages between a warmer climate and increased evaporative emissions from mobile sources (Rubin et al, 2006), increased electricity usage (Mideksa and Kallbekken, 2010), and increased wildfire activity over parts of the United States (Yue et al, 2013), all of which could lead to even greater health impacts from climate than shown here.…”
Section: Limitationscontrasting
confidence: 38%
“…Higher temperatures increase the demand for air conditioning in summer when ozone and PM concentrations are highest. Evaporative emissions of anthropogenic NMVOCs also increase, although the effect determined for mobile sources is relatively weak, in the range 1.3-5% K À1 (Cardelino and Chameides, 1990;Rubin et al, 2006).…”
Section: Implications For Air Quality Managementmentioning
confidence: 99%